Music Instructional to Develop Character Values for Early Childhood at Fishery Community Tambak Lorok Semarang City - Budiartati, Emmy; Jamaris, Martini; Yufiarti, Yufiarti (Universitas Negeri Semarang, 2018)
Every child has the music potency without exception, although they have different potential / talent of musical that is owned and viewed from the aspect of education. Early childhood music potential looks at everyday activities and it’s natural. The research was conducted at Paud Nanda Sifana, located in the fishery village of Tambak Lorok, Semarang City. The music instructional in early childhood includes; singing, clapping, and playing simple musical instruments in accordance to develop their character values. Character values that can be developed through music instructional such as; religious, honest, tolerance, the spirit of nationalism, the love of homeland, the love of peace, environmental care and others. From the results of observations that the authors carried out, found that the development of the characters values through music instructional formed in Paud Nada Sifana Tambak Lorok, seem less optimal and has not seen as the development of character values that should be happening to them. It is because the instructional in general is oriented to academic development in the form of learning calistung (reading, writing, arithmetic), so that the music instructional that can develop their character values get minimum portion.